Peningkatan Kemampuan Mengenal Huruf melalui Video Pembelajaran bagi Anak Tunagrahita kelas III di SLB Dharma Wanita Tana Toraja - Ingrid Fatricia Bernard; Triyanto Pristiwaluyo; Usman Usman (-, 2026)
This research was motivated by problems in recognizing letter in class III mentally retarded children at SLB Dharma Wanita Tana Toraja. The aim of this research is to find out: 1) The ability to recognize letter for mentally retarted children before implementing learning videos. 2) Ability to recognize letter for mentally retarded children after implementing learning videos. 3) Increasing the ability to recognize letter for mentally retarded children through the implementation of learning videos. The approach in this research is a quantitative approach with desckriptive research type. The subjects in this research were grade III mentally retarded children at SLB Dharma Wanita Tana Toraja with letters recognition ability test, observation and documentation as complementary data. The results of the study showed an increase in the ability to recognize letters in mentally retarded children. Before the implementation of the learning video, it was in the very poor category and after the implementation of the learning video, it improved and entered the capable category. The conclusion of this research is that there is an increase in the ability to recognize letters through the implementation of learning videos.